2015
DOI: 10.2298/vsp140401064g
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study on the influence of suturing material on oral wound healing

Abstract: The results of our clinical study point out that Vycril- rapid contributes more than catgut or Dexon to faster healing of human wounds, with fewer incidences of wound dehiscence and milder local reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…There is no ideal suture, but vegetal fibers allow the organization of the tissue with rapid healing similar to the silk suture used as a control. Other commercial sutures such as catgut, Dexon, and Vicryl have been reported to induce an inflammatory response [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no ideal suture, but vegetal fibers allow the organization of the tissue with rapid healing similar to the silk suture used as a control. Other commercial sutures such as catgut, Dexon, and Vicryl have been reported to induce an inflammatory response [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyglycolic acid (PGA) sutures have excellent strength and reduced tissue reactions [15]. Grazivoda et al stated that in the case of PGA sutures the inflammatory response was diminished when compared to other types of sutures [16]. Polyglycolic acid was the first synthetic absorbable suture that had a higher tensile strength [15].…”
Section: Resultsmentioning
confidence: 99%
“…Gazivado et al compared wound healing and the incidence of complications such as wound infection and local reactions with the use of different types of absorbable sutures (catgut, Dexon, and Vicryl). The results suggested that none of the suture materials hindered wound healing, and there was a low incidence of wound complications with all of the used suture materials that did not reach statistical significance [ 19 ]. Other reports advocate the use of catgut as an absorbable suture as it is absorbable, has good tensile strength, is more comfortable for the patients as it spares them the pain of suture removal, leads to excellent wound healing, and has comparable rates of complications to other absorbable and non-absorbable suture materials [ 14 , 15 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%